Facilitated isolation of rare recombinants by ligase chain reaction: Selection for intragenic crossover events in the Drosophila optomotor-blind gene. - Balles, J.; Pflugfelder, G.O. (Molecular and General Genetics, 1994)
Ligase chain reaction (LCR) was evaluated as a tool for the detection of point mutations. For the mutation studied, the specificity of the method is sufficient to detect the mutant allele in the presence of a 200-fold molar excess of the wild-type sequence. LCR was therefore employed in a genetic recombination experiment as a probe for a recessive lethal point mutation. LCR greatly facilitated the isolation of a rare recombinant originating from a crossover event in the 40 kb interval separating the lethal mutation and an enhancer trap insertion in the optomotor-blind locus. The recombinant will allow the study of gene control in situ, in a largely unperturbed regulatory environment.